(untitled) (International Journal of Mass Communication, 2024)
Boeing’s leadership faced significant criticism for its mishandling of the two 737 Max plane crashes that occurred within a six-month span. Since then, Boeing has been grappling with ongoing quality control issues with its 737 Max series, including a recent door plug failure on a 737 Max 9 mid-flight, and production flaws in the 787 Dreamliner, such as gaps between fuselage sections.This case study applies image repair theory (IRT) to explore Boeing’s crisis communication strategies in response to the 737 Max plane crashes. This study further investigates the application of the concepts of stealing thunder, framing hypothesis, and ethical apology, and their application in Boeing’s crisis management. The findings reveal that Boeing’s leadership employed both denial and mortification strategies; however, the timing and execution of these communications were flawed, leading to long-term reputational damage.Boeing’s failure to employ stealing thunder, effective framing, and delivering sincere apologies has hindered its ability to control the crisis narrative. Theoretical implications for IRT are discussed.